Business cycle synchronization: A regional perspective - Krzysztof Beck (Institute of Economic Research (IER), 2015)
Turmoil in euro area once more forces EU authorities to rethink future of further monetary integration. One of the most commonly used criterions for successful monetary in contemporary research is business cycle synchronization (BCS). Though BCS has been vastly described at country level, not as much attention has been put on the degree of BSC at regional level. Topic is important for 2 main reasons. The first is that determining degree of BCS at regional level can help in assessment of monetary policy effectiveness at country level, as well as giving point of reference for evaluation of perspective costs of participation in monetary union. The second is that there is theoretical dispute within the optimum currency areas literature between 'European Commission' and 'Krugman' view that can be resolve a great deal trough regional analysis. In order to assess BCS in EU Hodrick-Prescott, as well as Christiano and Fitzgerald filter to time series of real GDP for 24 countries, 82 NUTS 1, 242 NUTS 2 and 1264 NUTS 3 regions over the period of 1998-2010. Data was later used to create bilateral measures of BSC, which gave 276 observations on country level, 3321 on NUTS 1, 29161 on NUTS 2 and 798216 on NUTS 3 level. Results of the analysis support 'European Commission' view and show very high degree of BSC within EU countries. Country level analysis also reveals that within the EU there exist group of countries that could form effectively working monetary union based on BCS criterion.
Keywords: E32; E50; F44; R10; 330; business cycle synchronization; regional economics; optimum currency area theory; Hodrick-Prescott filter; European integration